Identifying predictors of response to oral non-steroidal anti-inflammatory drugs and paracetamol in osteoarthritis: a hypothesis-driven protocol for an OA Trial Bank individual participant data meta-analysis - Michael Doherty; Jie Wei; Yilin Xiong; Marienke van Middelkoop; Weiya Zhang; Monica S M Persson (BMJ Open)
Introduction Symptomatic treatments for osteoarthritis (OA) provide only small-to-moderate efficacy over placebo in randomised controlled trials (RCTs). Treatment guidelines therefore have emphasised the need to identify predictors of treatment response through subgroup and multiple regression analysis. Individual participant data (IPD) meta-analysis is recommended as an efficient approach for this purpose. To our knowledge, this has not been undertaken for oral non-steroidal anti-inflammatory drugs (NSAIDs), including paracetamol, in OA. In this IPD meta-analysis, we aim to identify RCTs with specific mechanistic features related to OA pain, such as joint inflammation. We hypothesise that NSAIDs may work better for participants with joint inflammation, whereas paracetamol may not.Methods and analysis A comprehensive literature search will be conducted on the databases of Web of Science, Embase, Medline, CINAHL, AMED and the Cochrane Library from 1 January 1998 to 1 December 2020. All RCTs related to oral NSAIDs or paracetamol including placebo-controlled trials in people with OA that have evaluated pain-related peripheral risk factors (eg, clinically detected knee effusion, synovial hypertrophy or effusion on imaging, knee morning stiffness, elevated serum C-reactive protein (CRP) level) and/or central pain risk factors (eg, pain elsewhere, depression, anxiety, sleep disturbance) will be retrieved. The outcome will be change in pain from baseline. Change in function and patient global assessment will also be included as outcomes if available. Investigators of all eligible trials will be contacted for IPD. Multilevel regression models will be used to identify predictors for the specific (active–placebo) and the overall treatment effect (change from baseline in active group).Ethics and dissemination No identifiable data will be included in this study and no formal ethics approval is required as no new data collection will be processed. Results of this hypothesis-driven IPD meta-analysis will be disseminated through conference presentations and publication in peer-reviewed journals.PROSPERO registration number CRD42020165098.